(untitled) (Bangladesh Journal of Plant Breeding and Genetics, 2007)
Thirty advanced breeding lines of deep-water rice were evaluated during T. Aman season (rainfed ecosystem) with a view to finding out variability and genetic association for grain yield and its component characters. All the tested characters showed significant variation. The highest genetic variability was obtained in filled grains/panicle followed by plant height. Panicles/plant, filled grains/panicle and grain yield had high genetic coefficient of variation and heritability in broad sense coupled with high genetic advance in percentage of mean. Panicle length, panicles/plant, plant height, filled grains/panicle and harvest index showed significant positive association with grain yield. Path coefficient analysis also revealed maximum positive and direct contribution of filled grain to grain yield followed by panicles/plant, 1000-grain weight and flag leaf area. Moreover, plant height had the highest indirect effect on grain yield through filled grains/panicle. Flag leaf area, harvest index and panicle length also had higher positive indirect effect on grain yield through filled grains/panicle. DOI: http://dx.doi.org/10.3329/bjpbg.v20i1.17024